Typical response of CD14++CD16– monocyte to knee synovial derived mediators as a key target to overcome the onset and progression of osteoarthritis - Saffery, Nik Syazana Izyan; Genasan, Krishnamurithy; Chan, Chee Ken; Ayob, Khairul Anwar; Teo, Seow Hui; Al-Fayyadh, Mohamed Zubair Mohamed; Othman, Iekhsan; Abidin, Syafiq Asnawi Zainal; Raman, Murali Malliga; Raghavendran, Hanumantha Rao Balaji; Kamarul, Tunku (Frontiers in Medicine, 2022)
Objective Synovitis with increased infiltration of immune cells is observed in osteoarthritis (OA). Given the inflammatory condition of synovitis, we explored the protein profile of OA synovium (OAS) and its effect on circulating monocytes activation, migration, and functional commitments. Methods Knee-synovium was acquired from end-stage OA (N = 8) and trauma patients (Trauma baseline control: TBC; N = 8) for characterization using H&E histology, IHC (iNOS), LCMS-QTOF, and MALDI-imaging. Response of peripheral blood monocytes to OAS conditioned-media (OACM) was observed using transwell (n = 6). The migrated cells were captured in SEM, quantified using phase-contrast microphotographs, and their activation receptors (CCR2, CXCR2, CX3CR1, and CD11b), pro-inflammatory genes, and phagocytic potential were studied using flow cytometry, gene expression array/qPCR, and latex beads (LB) phagocytosis assay, respectively. Results The Venn diagram displayed 119 typical proteins in OAS, while 55 proteins in TBCS. The STRING protein network analysis indicated distinctive links between proteins and gene ontology (GO) and revealed proteins associated with leukocyte-mediated immunity in OAS as compared to TBC. The MALDI-imaging showed typical localized proteins at 2234.97, 2522.61, 2627.21, 3329.50, and 3539.69 m/z and IHC confirmed pro-inflammatory iNOS expression in OA synovium. CD14++CD16– classical monocytes significantly migrated in OACM and expressed CCR2, CXCR2, and CD11b receptors, TNFRSF11A, MAPK1, S100A8, HSPB1, ITGAL, NFATC1, IL13RA1, CD93, IL-1β, TNF-α, and MYD88 genes and increased LB uptake as compared to SFM. Conclusion Our findings suggest that the differential protein profile of OA synovium and the classical monocytes migrated, activated, and functionally committed in response to these mediators could be of therapeutic advantage.